P- and SV-velocity structure of the South Portuguese Zone fold-and-thrust belt, SW Iberia, from traveltime tomography - Schmelzbach, C.; Zelt, C.; Juhlin, Christopher; Carbonell, R. (Blackwell Publishing Ltd, 2008)
Imaging the architecture of the shallow crust of the South Portuguese Zone fold-and-thrust belt is essential to extend surface mapped geological information to depth and to help in developing models of the ore-bearing Iberian Pyrite Belt part of the Variscan orogeny. The recently acquired IBERSEIS seismic-reflection data set provides, for the first time, detailed images of the entire crust, but source-generated noise masks the earliest reflections and limits the shallowest observed signals to depths >500 m. We inverted P- and SV first-arrival traveltimes for the smoothest minimum-structure velocity models, imaging the shallowest few hundreds of metres along four in total ~60-km-long profiles. A comparison of a 2-D and 2.5-D (3-D forward and 2-D inverse problem) crooked-line inversion scheme revealed that the crooked-line geometry has a negligible effect on the final images. Resolution of the final preferred models was assessed on the basis of an extensive series of checkerboard tests, showing a slightly lower resolution capability of the SV-data due to greater data uncertainty, fewer number of picks and more limited source-receiver offsets compared with the P-data. The preferred final models compare favourably with the mapped surface geology, showing relatively high and uniform velocities (>5.25 km s-1) for the flysch group in the southern part of the investigation area. Low velocities (~4.5 km s-1) are found for the 'La Puebla de Guzman antiform' in the centre of the investigation area, where the phyllite-quartzite group is exposed. Velocities fluctuate the most along the northernmost ~20 km. Velocity variations reflect more the state of tectonic deformation than being directly correlated with the mapped lithologies. Based on a comparison with coincident seismic-reflection data along the southern half of the area, we suggest that two areas of low to intermediate ratios (~1.85-1.9) correspond to occurrences of thick and less deformed flysch-group units, whereas high VP/VSV ratios (~1.95) are interpreted to indicate increased porosity due to intense fracturing. © 2008 The Authors Journal compilation © 2008 RAS.